A million years of music : the emergence of human modernity - Tomlinson, Gary (Zone Books, 2015)
What is the origin of music? In the last few decades this centuries-old puzzle has been reinvigorated by new archaeological evidence and developments in the fields of cognitive science, linguistics, and evolutionary theory. In this path-breaking book, renowned musicologist Gary Tomlinson draws from these areas to construct a new narrative for the emergence of human music. Starting at a period of human prehistory long before Homo sapiens or music existed, Tomlinson describes the incremental attainments that, by changing the communication and society of prehuman species, laid the foundation for musical behaviors in more recent times. He traces in Neandertals and early sapiens the accumulation and development of these capacities, and he details their coalescence into modern musical behavior across the last hundred millennia. But 'A Million Years of Music' is not about music alone. Tomlinson builds a model of human evolution that revises our understanding of the interaction of biology and culture across evolutionary time-scales, challenging and enriching current models of our deep history. As he tells his story, he draws in other emerging human traits: language, symbolism, a metaphysical imagination and the ritual it gives rise to, complex social structure, and the use of advanced technologies. Tomlinson's model of evolution allows him to account for much of what makes us a unique species in the world today and provides a new way of understanding the appearance of humanity in its modern form.